Identification of the behavior of properties of a cold-hardening glass-liquid mixture with propylene-carbonate different in dosing components - Akimov, Oleg; Penzev, Pavel; Marynenko, Dmytro; Saltykov, Leonid (Technology audit and production reserves, 2018)
The object of research are models that describe the effect of liquid glass and propylene carbonate as a hardener of the molding mixture on its properties. One of the most problematic places is determination of the behavior of the properties of the mixture under conditions of deviation from the optimal values of the content of liquid glass as a binder and propylene carbonate as a hardener. The definition of such behavior is important because it will improve the processes of regulating the loading of mixers in automated systems for the manufacture of the mixture in foundries. The methods of canonical transformation of response surfaces are used, describing the effect of the content of liquid glass and propylene carbonate on the following properties of the mixture: survivability, compressive strength after 1 hour, after 3 hours, after 24 hours, crumbling. The mechanisms of chemical reactions that lead to the process of mixture curing are described and the possibility of obtaining qualitative characteristics of the mixture is substantiated by analyzing the chemistry of the process. An analytical description of the response surface in the stationary region in the factor space transformed after the standard procedure “liquid glass content – propylene carbonate content” is obtained in canonical form. Such a transformation allows to estimate the nature of the response surface by analyzing the ratios of the eigenvalues included in its canonical description in terms of size and sign. Such an approach used has an important feature, since it allows one to directly determine the behavior of the properties of the mixture in the event of deviations from the optimal values of the content of liquid glass and propylene carbonate. This makes it possible to determine measures or technical solutions for the work or to improve the systems for regulating dosing processes in automated systems for the production of a mixture in foundries. At the same time, adaptation to any known dosing systems of binder and hardeners of cold-hardening mixtures is possible. This opens up prospects for stabilizing the quality of the molding or core mixture and improving the quality of shaped castings for mechanical engineering, in particular, responsible and basic cast parts of internal combustion engines (ICE).